The bone density diet a revolutionary programme that helps you to retain strong, healthy bones at any age and reduces the risk of osteoporosis - Kessler, George (Vermilion, 2000)
A programme that helps you build and maintain strong, healthy bones and reduce the health risks associated with low bone density, including osteoporosis. It helps you to assess your own low density risk and then offers a complete three week eating plan. It also shows you how to include weight-bearing exercises into everyday life.